Ethical and Value Conflicts’ Impact on Multicultural Teaching - Andriana, Rifa; Khairat, Annisaul (International Journal of Education, Management, and Technology, 2023)
Values ​​and ethics are very important and necessary in multicultural teaching so that teaching can take place effectively and optimally. Students and teachers must contribute to each other in realizing effective teaching by applying good and polite values ​​and ethics. In multicultural teaching, not everything goes according to what is expected. Obstacles often arise, making it a problem or conflict of values ​​and ethics in multicultural teaching. The existence of differences in ethnicity, nation, culture, economy and background between fellow students and teachers is one of the factors in the emergence of conflicts in values ​​and ethics. The aim of this research is to describe the value and ethical conflicts that occur in multicultural teaching, as well as finding solutions that can be implemented to minimize value and ethical conflicts in multicultural teaching. This research uses quantitative methods, data obtained through distributing questionnaires. The questionnaire was distributed using Google Form, stating several statements to be answered by respondents. The results of this research explain that there is a conflict of values ​​and ethics in multicultural teaching which can have an impact on the multicultural teaching process. The implication of this research is to find out what value and ethical conflicts exist in multicultural teaching and find solutions to these problems so that the teaching process can take place optimally and run effectively.